1982
DOI: 10.1002/bjs.1800691317
|View full text |Cite
|
Sign up to set email alerts
|

The early diagnosis of massive acute intestinal ischaemia

Abstract: Intestinal ischaemia with ensuing gangrene has been a serious clinical problem. Delay in diagnosis has inevitably led to either massive gut resection or death. It has been shown that the bowel contains high concentrations of both organic and inorganic phosphate. With gut ischaemia, phosphate is released from the bowel and elevated concentrations may be measured in peripheral blood, peritoneal fluid and urine. Associated leucocytosis and acidosis constitute a diagnostic laboratory triad. The alteration in gut p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 3 publications
0
13
1
Order By: Relevance
“…Phosphate had no association with bowel ischemia in this study, which is a departure from the findings of Jamieson [18], who found phosphate to be significantly increased (in 80% of patients) in massive bowel ischemia. He however did not define what massive was.…”
Section: Discussioncontrasting
confidence: 99%
“…Phosphate had no association with bowel ischemia in this study, which is a departure from the findings of Jamieson [18], who found phosphate to be significantly increased (in 80% of patients) in massive bowel ischemia. He however did not define what massive was.…”
Section: Discussioncontrasting
confidence: 99%
“…Admission leukocyte counts of 12.000 -40,000 were seen in all of our patients and in the patient described by Cryer and Kissane [14], Acidemia devel- oped only late and was usually present only after an abdominal catastrophe was clinically apparent [18]. Mild hyperphosphatemia was present in 2 of the 4 patients tested, but is not a useful indicator of ischemic bowel in the renal failure patient (table III) [19]. The mortality of acute mesenteric ischemia in our patients plus those pre viously described is similar to that reported in series on nonrenal patients [20,21].…”
Section: Discussionmentioning
confidence: 83%
“…The liver is largely responsible for the absorption of Pi, and as a result large volumes need to be produced by intestinal infarction before it becomes significantly raised in serum [93]. Clearly, Pi can be measured in biofluids such as urine, serum and peritoneal fluid without the need for NMR, but only with a statistical sensitivity of approximately 80% in human clinical studies [94].…”
Section: Analysis Of Intestinal I/r By Nmr Spectroscopymentioning
confidence: 99%